2019
DOI: 10.1093/ofid/ofz023
|View full text |Cite
|
Sign up to set email alerts
|

Substance Use, Demographic and Socioeconomic Factors Are Independently Associated With Postpartum HIV Care Engagement in the Southern United States, 1999–2016

Abstract: BackgroundRetention in care (RIC) and viral suppression (VS) are associated with reduced HIV transmission and mortality. Studies addressing postpartum engagement in HIV care have been limited by small sample size, short follow-up, and a lack of data from the Southeast United States.MethodsHIV-positive adult women with ≥1 prenatal visit at the Vanderbilt Obstetrics Comprehensive Care Clinic from 1999 to 2015 were included. Poor RIC was defined as not having ≥2 encounters per year, ≥90 days apart; poor VS was a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…LTFU, which is defined here as 12 months without care before study closure, but elsewhere, has been classified as the first 3-, 6-or 12-month gap in care). [20,35] Other potential barriers to inference include unmeasured confounding, potential selection biases (e.g. if HIV testing and care referral practices differed between women diagnosed during and before pregnancy, or the late presentation and HIV diagnosis of some women delayed ART initiation), and changes in clinical and programme management, such as guidelines for cART use during pregnancy and universal treatment (under WHO guidance from 2015), over an admittedly long study period spanning nearly 20 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LTFU, which is defined here as 12 months without care before study closure, but elsewhere, has been classified as the first 3-, 6-or 12-month gap in care). [20,35] Other potential barriers to inference include unmeasured confounding, potential selection biases (e.g. if HIV testing and care referral practices differed between women diagnosed during and before pregnancy, or the late presentation and HIV diagnosis of some women delayed ART initiation), and changes in clinical and programme management, such as guidelines for cART use during pregnancy and universal treatment (under WHO guidance from 2015), over an admittedly long study period spanning nearly 20 years.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors found to be associated with a higher risk of LTFU in prior work are unemployment, lack of basic needs such as electricity in the home [18], substance use, lower educational attainment [20] and social factors that include fear of disclosure, lack of social support and negative experiences with providers [21]. It has also been shown that this population remains vulnerable to suboptimal health outcomes and lack of clinical care due to increased responsibilities, emotional stress and stigma related to HIV disclosure during pregnancy [21].…”
Section: Discussionmentioning
confidence: 99%
“…Substance use is a risk factor for multiple negative health outcomes, including transmission of STDs and HIV. [1][2][3][4][5] A unique aspect of primary care is the understanding of the complex interplay between physical and behavioral health. Substance use and overuse are important components of behavioral health that can have a powerful impact on physical health.…”
Section: Introductionmentioning
confidence: 99%